Why is it so hard to reduce harm from medicines? - Andrew Rochford (Future Healthcare Journal)
Pharmacotherapy is the most common therapeutic intervention in healthcare, but more than 200 million medication errors occur every year in England alone. This may in part reflect greater awareness and better reporting; however, the incidence of patient harm from medication has remained broadly unchanged for decades, despite concerted national campaigns and global safety initiatives. Rapid technological and therapeutic advances together with the complexity of modern healthcare make reducing harm from medicines more challenging than ever. This opinion piece will provide a perspective on some of those challenges, as well as highlighting areas of best practice and emerging work. While system and process improvements are required, individual clinicians need to remain vigilant and reflect on medications at each patient interaction.